Islam Hadhari approach in Malaysia: A preliminary research - Osman Talib; Badlihisham Mohd Nasir (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2008)
Today, the concept of Islam al-Hadhari that dominates over the style of leadership shown by the fifth Malaysian Prime Minister, Dato’ Seri Abdullah bin Haji Ahmad Badawi has been much talked about. Being coupled with its new concept in the context of Islamic development in this country Islam al-Hadhari has been too controversial that it is accused of disrespect of Islam. Nevertheless, this concept should not be simply sidelined though the possibility of it having some defects is undeniable. We should, instead attempt before making any judgment on the matter to comprehend it from the perspective of one who initiated it. He must have a good reason and a noble intention in making such a policy. Instead, we better highlight this concept in the light of its main and official resources , so that we can get the true perception of the concept without being carried away by the wrong interpretation of some parties. The door of dialogue concerning the issue is open to all, provided that their discussion is objective, scientific and unbiased in search of Allah’s pleasure. This paper is a preliminary attempt to focus on a brief picture of the background of Islam Hadhari. It’s important aspects, such as its definitions,objectives and characteristics are also dealt with in this paper